Can a bonus overcome moral hazard? An experiment on voluntary payments, competition, and reputation in markets for expert services - Vera Angelova; Tobias Regner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
Interactions between players with private information and opposed interests are often prone to bad advice and inefficient outcomes, e.g. markets for financial or health care services. In a deception game we investigate experimentally which factors could improve advice quality. Besides advisor competition and identifiability we add the possibility for clients to make a voluntary payment, a bonus, after observing advice quality. We observe a positive effect on the rate of truthful advice when the bonus creates multiple opportunities to reciprocate, that is, when the bonus is combined with identifiabilitiy (leading to several client-advisor interactions over the course of the game) or competition (allowing one advisor to have several clients who may reciprocate within one period). Moreover, identifiability significantly increases truth-telling under competition.
Keywords: C91; D03; D82; G20; I11; 330; asymmetric information; principal-agent; expert services; deception; sender-receiver game; reciprocity; reputation; experiments; voluntary payment; competition